Antimicrobial efficiency of chitosan coating enriched with bioactive compounds to improve the safety of fresh cut broccoli - Alvarez, María Victoria (2013)
Antimicrobial properties of chitosan (CH) coatings and CH enriched with bioactive compounds (BC) and essential oils (EO) were determined by in vitro and in vivo assays on minimally processed broccoli. The efficiency of CH plus BC/EO in improving the safety of broccoli was tested against the native microflora. Also, its effects on the survival of Escherichia coli and Listeria monocytogenes inoculated in broccoli were evaluated. In vitro assays performed in tea tree, rosemary, pollen and propolis demonstrated significant inhibitory effects on E. coli and L. monocytogenes counts while pomegranate and resveratrol presented reduced activity. In vivo application of these BC on broccoli exerted a bacteriostatic effect on mesophilic and psychrotrophic populations except for rosemary. The application of CH alone or enriched with BC/EO resulted in a significant reduction in mesophilic and psychrotrophic counts. Between days 5 and 7, significant reductions (2.5 log) were observed in samples treated with CH þ BC. The enrichment with BC improved the antimicrobial action of CH. The application of these coatings did not introduce deleterious effects on the sensory attributes of broccoli. CH coatings enriched with BC/EO were a good alternative for controlling not only the microorganisms present in broccoli, but also the survival of E. coli and L. monocytogenes.